CONTACT MECHANICS BEHAVIOR OF RUBBER TUBE OF DOWN-HOLE PACKER - HAN ChuanJun; CHEN Fei; ZHANG Jie; YU Cheng (Jixie qiangdu)
To study frictional contact problem between rubber tube and the casing,The friction coefficient is measured with Vertical universal friction and wear testing machine that type is MMW- 1. Based on Mooney-Rivlin model of rubber material,using the principle of penalty function and coulomb friction and Combining with rubber nonlinear large deformation problems,the frictional contact problem of Rubber tube and casing is analyzed by the finite element with measured data. The results shown that the friction coefficient of contact is the maximum and 0. 514 in the absence of lubricant,the minimum and 0. 122 under oil lubrication,and others is 0. 122 0. 514. With the increase of friction coefficient,friction stress increase gradually,but the contact pressure decrease as a whole. Equivalent stress of rubber tube first increases then decreases. When friction coefficient is0. 3,contact pressure can be better. With the increase of axial loading,contact pressure,friction stress and the equivalent stress of packing element increases gradually. Keep axial loading,the width of rubber tube has greatly influenced on contact problem.Finally,the structure of rubber tube has been optimized to obtain a better structure which is entire circular arc.